Toolkit of material resources management in lean production at engineering enterprises - Smirnov Artyom (Peter the Great St. Petersburg Polytechnic University, 2021)
Continuous improvement of material resources management tools based on the principles of lean production in production management allows managers of enterprise to increase the economic efficiency of operating activities and gain competitive advantages. Sheet metal cutting is the main technological process with sheet metal taking a significant share of production material costs at many engineering enterprises. Therefore, the task of increasing of the material utilization rate is relevant in terms of increasing the economic efficiency of the enterprise and rational use of natural resources. Introduction of rational cutting algorithms is the main direction of solving this task. However, in order to eliminate arising losses when cutting sheet metal, it is necessary to pay attention to the questions of reasonable sorting of material resources after cutting into groups of business and non-business material resources and the organization of their management accounting. The purpose of the research is to develop tools of material resources management in lean production for sheet metal cutting at engineering enterprises with single or serial types of production. The paper proposes the terminological apparatus of the study, develops a method for material resources sorting after sheet metal cutting, and substantiates the possibility of increasing the economic efficiency of sheet metal rational cutting taking into account business material resources. The practical recommendations for organization of management accounting of material resources after sheet metal cutting were also proposed in the research. It should be noted that using information technologies in the process provides managers with operational and substantiated information for making economic effective and timely management decisions. Thus, as a result of the research, the theoretical and practical aspects of material resource management after cutting were developed. The practical significance of the research consists in the possibility of mastering the developed proposals in engineering production for improving the process of sheet metal cutting in order to reduce technological costs, optimize the costs structure or increase net income.